2013
DOI: 10.5194/acp-13-10373-2013
|View full text |Cite
|
Sign up to set email alerts
|

Ozone trends derived from the total column and vertical profiles at a northern mid-latitude station

Abstract: Abstract. The trends and variability of ozone are assessed over a northern mid-latitude station, Haute-Provence Observatory (OHP: 43.93 • N, 5.71 • E), using total column ozone observations from the Dobson and Système d'Analyse par Observation Zénithale spectrometers, and stratospheric ozone profile measurements from light detection and ranging (lidar), ozonesondes, Stratospheric Aerosol and Gas Experiment (SAGE) II, Halogen Occultation Experiment (HALOE) and Aura Microwave Limb Sounder (MLS). A multivariate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 46 publications
16
65
0
Order By: Relevance
“…In fact, the influence of the solar cycle on ozone is difficult to discern in the lower stratosphere (see expanded axis). This is consistent with results from previous studies, which have shown that the solar cycle effect on ozone maximizes around 35 km and weakens in the lower stratosphere (Egorova et al, 2004;Lee and Smith, 2003;Newchurch et al, 2003). The QBOdriven anomalies in NAT-h (Fig.…”
Section: Variability In Waccm Natural and Control Simulationssupporting
confidence: 82%
See 3 more Smart Citations
“…In fact, the influence of the solar cycle on ozone is difficult to discern in the lower stratosphere (see expanded axis). This is consistent with results from previous studies, which have shown that the solar cycle effect on ozone maximizes around 35 km and weakens in the lower stratosphere (Egorova et al, 2004;Lee and Smith, 2003;Newchurch et al, 2003). The QBOdriven anomalies in NAT-h (Fig.…”
Section: Variability In Waccm Natural and Control Simulationssupporting
confidence: 82%
“…The NAT-derived estimate of the change in upper- stratospheric ozone from solar maximum to solar minimum is approximately 2-4 %. This is in agreement with results from previous observational and model-based studies (Lee and Smith, 2003;Newchurch et al, 2003;Randel and Wu, 2007). NAT also shows longer-timescale variability in upperstratospheric ozone concentrations in response to solar insolation changes over multiple decades to centuries.…”
Section: Variability In Waccm Natural and Control Simulationssupporting
confidence: 82%
See 2 more Smart Citations
“…In order to improve the fit, it is important to study dynamical processes to find their effects on long-term changes in ozone distribution in middle latitudes and in the upper stratosphere. Several studies have addressed the significance of contributions of dynamical processes to long-term ozone changes (Appenzeller et al, 2000;Weiss et al, 2001;Wohltmann et al, 2007;Mäder et al, 2007;Rieder et al, 2010;Frossard et al, 2013;Rieder et al, 2013;Nair et al, 2013). Several papers (Harris et al, 2008;WMO, 2007) found that a significant part of the change in total ozone after the middle of the 1990s and until 2005 was caused by dynamical variability.…”
Section: Atmosmentioning
confidence: 99%